2023
DOI: 10.3390/jmmp7010031
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Processing Conditions in the Performance of Purging Compounds for Polypropylene Injection Molding

Abstract: Purging is a fundamental process in the injection molding sector, aiding in color transition, material shifts, and the removal of contaminants. The purging compounds can be classified according to physical or chemical mechanisms and are affected by processing parameters, such as temperature, pressure, or soaking period. Despite some studies on the effect of processing parameters in purging action, an analysis of the rheological behavior and physico-chemical changes is still required for a deeper understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In the present work, the unreinforced PP samples have either amorphous or crystalline behavior depending on the process conditions. According to Carrasco et al [ 38 ], the differential scanning calorimetry (DSC) of the virgin PP homopolymer at its melting and crystallization temperatures were 164.68 °C and 134.17 °C, respectively, and the material was 55.12% crystalline. From the numerical analysis of Table 4 data and Figure 17 , it is observed that polypropylene behaves as a crystalline material when processed at higher temperatures and pressures.…”
Section: Resultsmentioning
confidence: 99%
“…In the present work, the unreinforced PP samples have either amorphous or crystalline behavior depending on the process conditions. According to Carrasco et al [ 38 ], the differential scanning calorimetry (DSC) of the virgin PP homopolymer at its melting and crystallization temperatures were 164.68 °C and 134.17 °C, respectively, and the material was 55.12% crystalline. From the numerical analysis of Table 4 data and Figure 17 , it is observed that polypropylene behaves as a crystalline material when processed at higher temperatures and pressures.…”
Section: Resultsmentioning
confidence: 99%